A half-day seminar on dealing with recovery in the construction and civil engineering sector delegate information : Tuesday 7 December 1993 at the Institution of Civil Engineers, London. (Thomas Telford, 1993)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.